Frederick H. Hartmann and the relations of nations - D’Alessio Ipinza, Fernando (2020)
Frederick Hartmann was born in New York in 1922 and died in 2015 at the age of 93. He graduated from the University of California at Berkeley, he joined the US Navy in the accelerated program during World War II and took part in nine invasions including that of Palau, Leyte, Linguyen, Gulf and Okinawa and was award with 7 battle stars. In 1946, he enrolled in the Princeton University Graduate School program, obtaining aPhD in Politics in 1949. He was professor at the University of Florida in 1948 where he was quickly promoted to associate professor and then to full professor. Hartmann commanded a division of the Naval Reserve in Gainesville, Florida and was promoted to Captain in 1966. That year he accepted a new position created at the United States Naval War College in Newport, Rhode Island, where he served for 20 years as Professor of Political Science and was the senior adviser to nine presidents of the Naval War College. His prolific literary production led him to write fifteen books, all of them very well known, including his most important ones: The Relations of Nations and The Conservation of Enemies. This author as an Alum of the US Naval War College is honored to attempt to revive his legacy, in this short article, for the prestigious Journal of the Peruvian Society of International Law, in which I try to revisit his most famous book: The Relations of Nations written in 1957 with six editions and translated into many languages, being used in international business schools, war schools, and foreign policy schools in many countries. The central theme of this article is the focus of the curriculum of the US Naval War College which are the internationalrelations and the politics and strategy in the development of nations.